Producing Online Youth Fiction in a Nordic Public Service Context - Andersen, Mads Møller; Sundet, Vilde Schanke (VIEW Journal of European Television History and Culture, 2019)
This article investigates the conditions for making online youth fiction in a public service context at a time when young people increasingly are abandoning both legacy mass media and linear flow television to consume and share content online. The article’s starting point is the production of online youth fiction in two Nordic public service institutions, the Norwegian NRK and the Danish DR, and it discusses how digitisation and new competitors present both challenges and opportunities for institutions such as these. Furthermore, the article discusses the organisation of online youth fiction in both institutions and investigates how organisational strategies and production cultures come into play in each of these broadcasters’ early signature youth series: the widely popular online teen drama SKAM (NRK, 2015-2017) and the far less known youth series Anton 90 (DR, 2015). Our findings show that it was the pressure imposed by digitisation and new competitors that led these institutions to take new risks with their youth fiction production, changing their production patterns to make short-form drama series tailored to online streaming, and ultimately treating online youth fiction as a distinctly different task than “regular” fiction.